2011
DOI: 10.1073/pnas.1017837108
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic neuropeptide release induced by octopamine without Ca 2+ entry into the nerve terminal

Abstract: Synaptic release of neurotransmitters is evoked by activity-dependent Ca 2+ entry into the nerve terminal. However, here it is shown that robust synaptic neuropeptide release from Drosophila motoneurons is evoked in the absence of extracellular Ca 2+ by octopamine, the arthropod homolog to norepinephrine. Genetic and pharmacology experiments demonstrate that this surprising peptidergic transmission requires cAMP-dependent protein kinase, with only a minor contribution of exchange protein activated by cAMP (epa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…The results of our work suggest that triggering of CGRP‐containing LDCVs exocytosis requires not only the mandatory release of calcium from the ryanodine‐sensitive Ca 2+ ‐stores but also the subsequent activation of CaMKII. Taking into account the data obtained at Drosophila NMJs (Shakiryanova et al., 2007, 2011), our results suggest that conservative signaling pathway exists in NMJs of different species, which regulates the exocytosis of LDCVs via RyRs and CaMKII. Interestingly, the increase in ACh quantal size during exogenous CGRP application could not be prevented by CaMKII blocking.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The results of our work suggest that triggering of CGRP‐containing LDCVs exocytosis requires not only the mandatory release of calcium from the ryanodine‐sensitive Ca 2+ ‐stores but also the subsequent activation of CaMKII. Taking into account the data obtained at Drosophila NMJs (Shakiryanova et al., 2007, 2011), our results suggest that conservative signaling pathway exists in NMJs of different species, which regulates the exocytosis of LDCVs via RyRs and CaMKII. Interestingly, the increase in ACh quantal size during exogenous CGRP application could not be prevented by CaMKII blocking.…”
Section: Discussionmentioning
confidence: 67%
“…Our suggestion is supported by previous results describing that the pool of the LDCVs is localized away from the extracellular calcium influx at the active zones (Pécot‐Dechavassine & Brouard, 1997), as well as ryanodine‐sensitive Ca 2+ ‐stores (Bouchard, Pattarini, & Geiger, 2003). In addition, the RyR‐mediated LDCV mobilization, trafficking, and exocytosis have been recently described at Drosophila NMJs (Shakiryanova, Zettel, Gu, Hewes, & Levitan, 2011; Shakiryanova et al., 2007; Wong, Shakiryanova, & Levitan, 2009). …”
Section: Discussionmentioning
confidence: 98%
“…In comparison to minor workers, defensive majors have more 5-HT-immunoreactive cells in primary visual regions, more extensive serotonergic varicosities in sensory and integrative brain regions [67], and more elaborate axonal arborization in a serotonergic neuron integral to sensory integration [27]. Although relationships between neuromodulators and circuit development have been described in other taxa [68,69], the influence of neuroanatomical differences in 5-HT circuitry on 5-HT signalling and behaviour remains to be studied in ants. In O. smaragdina, major and minor worker differences in endogenous OA titres may alter circuitry to generate subcaste-related aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these mechanistic differences in DCV biology have been probed at Drosophila synapses using transgenic animals expressing an artificial neuropeptide-GFP-tagged rat atrial natriuretic factor peptide (ANF-GFP) (Rao et al 2001a). This transgenic line has proved highly valuable for DCV biology, revealing mechanisms of activity-dependent recruitment of DCVs (Shakiryanova et al 2005), DCV capture at active terminals (Wong et al 2012;Bulgari et al 2014), presynaptic ER-dependent Ca 2+ release driving DCV fusion (Shakiryanova et al 2007(Shakiryanova et al , 2011, and partial depletion of DCV contents upon release (Wong et al 2015). In addition to aspects of DCV release and trafficking, studies have revealed the role of the basic helix-loop-helix transcription factor Dimmed in driving neuroendocrine cell fate, including its role in regulating the expression of specific DCV proteins (Hewes et al 2006;Hamanaka et al 2010;Park et al 2011Park et al , 2014.…”
Section: Dense Core Vesicle Releasementioning
confidence: 99%